Effect of high-strain cold rolling on microstructure, texture, and mechanical properties of pure zinc for biomedical applications - Jin Cui; Hengyang Yu; Yong Gong; Poorva Sharma; Ashwini Kumar; Lianjun Sun (Materials Research Express)
The application of pure zinc (Zn) in biodegradable implants is limited by its mechanical strength. This study investigates the microstructural and textural evolution of pure Zn induced by high-strain cold rolling (up to 98% reduction) and its consequent effect on microhardness, employing x-ray diffraction (XRD), electron backscattered diffraction (EBSD), and Vickers hardness testing. The results indicate that cold rolling significantly refines the grain structure through discontinuous dynamic recrystallization (DDRX). A slight increase in grain size to 50 μm was observed at 98% reduction, which is attributed to adiabatic heating. The texture evolved from a basal orientation to a more randomly oriented state and then reverted to a basal texture. This transition is closely associated with {10–12}〈10-1-1〉 tensile twinning and DDRX, wherein the formation of the DDRX texture occurred via selective growth. Microhardness exhibited a minor decrease at 96% reduction due to the weakening of the 〈11–20〉//RD texture, followed by a significant reduction at 98% reduction, attributed to the softening effect of DDRX. Additionally, adiabatic heating activated {10–10}〈1–210〉 prismatic slip at elevated strains. This slip system may interact synergistically with {0001}〈11–20〉 basal, {11–22}〈−1–123〉 second-order pyramidal slip, and twinning to facilitate DDRX.